Program Edukasi Kesehatan Berbasis Keluarga pada Self-Management Pasien Hipertensi - Zahirah, Esa; Pahria, Tuti; Kurniawan, Titis (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to examine further how families are involved in family-based self-management education for hypertension sufferers. The method used is a scoping review with PCC (Population, Context & Concept) components. Population is